Perovskite Solar Cells for Extreme Environments: Tailoring Material Design and Exploring New Opportunities - Kim, Wooyeon; Koo, Bonkee; Ko, Min Jae (Nano-Micro Letters, 2026)
A stable and independent power supply is essential in extreme environments, where access to power infrastructure or opportunities for resupply are limited. Conventional batteries and fuel-powered generators are often heavy and require specialized maintenance. In contrast, solar cells can generate electricity directly from sunlight without reliance on external fuel sources. Among next-generation photovoltaic technologies, perovskite solar cells (PSCs) offer notable advantages, including tunable bandgaps and a high absorption coefficient, which enable spectral matching and stable operation even under low-irradiance conditions. Furthermore, PSCs are thin, lightweight, and mechanically flexible, allowing integration into mobile electronics and aerial systems such as drones and satellites. Despite these advantages, PSCs were previously considered unsuitable for deployment in harsh environments due to the intrinsic instability of perovskite absorbers, which are prone to degradation under external stressors such as heat, humidity, and continuous radiation. Recent progress in interface passivation, encapsulation, and the development of self-healing perovskite materials has significantly enhanced the long-term stability of PSCs, thereby enabling their potential application in extreme environmental conditions. In this review, we categorize the environmental threats relevant to space, underwater, desert, and polar regions, and analyze the specific stressors associated with each setting. We then examine recent technological advances that address these stressors and evaluate the practical feasibility of PSC operation under such conditions. The review concludes by identifying remaining challenges and offering perspectives on the future implementation of PSCs in extreme environments. Highlights: 1 This review discusses the deployment of perovskite solar cells (PSCs) in extreme environments such as space, underwater, desert, and polar regions. 2 We examine recent strategies to enhance the long-term stability of PSCs through defect passivation, interface engineering, encapsulation, and self-healing perovskites, with respect to degradation mechanisms under continuous irradiation, elevated temperatures, and high humidity. 3 Guidelines are also proposed for future stability testing and practical performance criteria that PSCs must satisfy for reliable operation under extreme environmental conditions.